Fully bio-based thiol-ene photocured thermosets from isosorbide and tung oil - ÇAKMAKÇI, EMRAH (WILEY, 2020)
Direct preparation of coatings from neat vegetable oils without any pretreatment or modification is an elegant way of demonstrating the potential of renewable sources and it is also in line with the principles of Green Chemistry. In this work, photocured coatings were prepared from tung oil (TO), hazelnut oil (HN), and isosorbide. First, a dithiol derivative of isosorbide (ISTMP) was synthesized and then mixed with TO, HN, and a cationic photoinitiator. For comparison, formulations were also prepared by using two different commercial thiol compounds. Coating formulations were applied onto glass substrates and cured under UV light where oxidative polymerization and photoinitiated thiol-ene addition reactions took place concomitantly. Double bond conversion percentages, thermal degradation properties, water contact angles, and surface hardness of the coatings were determined. Furthermore, a model reaction between ISTMP and oleic acid was performed to prove that ISTMP reacts with the fatty acid. ISTMP containing formulation displayed a fast initial double bond conversion and its water contact angle value was found as 88 +/- 3 degrees. Rigid and thermally stable isosorbide ring improved both the thermal properties and the surface hardness of the coatings.
Keywords: biomass; isosorbide; renewable resources; thermosets; thiol-ene; SOYBEAN-OIL; POLYMERIC MATERIALS; GREEN CHEMISTRY; VEGETABLE-OILS; UV; COATINGS; PERFORMANCE; NETWORKS